Addressing gendered affordances of the platform economy: The case of UpWork - Elisabetta Stringhi (Internet Policy Review, 2022)
This study investigates UpWork affordances and their implications for female freelancers experiencing different forms of cyberviolence. Building up on a theoretical framework to situate the concept of affordances, gendered affordances and cyberviolence within a platform economy context, I use UpWork as a relevant case study to assess how online platforms that intermediate labour transactions present gendered affordances contributing to cyberviolence against women. I analysed the discussions of female users and freelancers in UpWork in line with the digital methods approach, by conducting a qualitative digital ethnographic analysis. These discussions serve as a foundation for a subsequent critical analysis of UpWork terms of service, to gain a wider understanding of how the digital platform controls information flows and models interactions between different categories of users. The findings suggest that UpWork affordances are gendered affordances, as they allow male users different conducts, as opposed to female freelancers, entrepreneurs, or users. I conclude that, while UpWork core features are allegedly neutral, they enable gendered affordances widening the gender gap in digital market transactions by facilitating the occurrence of cyber violence against women.
Keywords: 300; Digital platforms; Women; Platform economy; gender; Inequality; Cybercrime